Addressing food system transformation, food security, and deforestation in Indonesia: Challenges and opportunities - Laborde Debucquet, David; Olivetti, Elsa B.; Piñeiro, Valeria; Illescas, Nelson (International Food Policy Research Institute, 2024)
This study identifies food system interventions with high transformational potential for Indonesia by utilizing the MIRAGRODEP a multi-region, multisector computable general equilibrium model to analyze policy scenarios. Our findings reveal a range of economic, social, and environmental impacts. Initiatives such as social safety nets and food stamps can enhance affordability, while repurposing farm subsidies can improve socio-economic sustainability. Comprehensive policy packages that include social safety nets, repurposing agricultural supports, environmental regulation and investment in sustainable production, can lead to substantial GDP growth, poverty reduction, and dietary enhancements. However, each intervention presents distinct trade-offs between economic gains and environmental implications. This analysis underscores the need for a holistic policy approach when trying to achieve multiple sustainability goals. Implementing a blend of policies designed to promote environmental, social, and economic sustainability simultaneously could drive Indonesia towards a sustainable and resilient food system, addressing the complex interplay between economic development, environmental conservation, and improved nutrition.